Предмет: Алгебра,
автор: аза55
Пожалуйста помогите решить.
а) (х^2+3)(x^2-1)=(1+x^2)^2+x
б) (2x-5)^2-(2x-3)(2x+3)=0
Ответы
Автор ответа:
0
а) х = -4;
б) х = 1,7.
(Решение на картинке)
б) х = 1,7.
(Решение на картинке)
Приложения:
![](https://files.topotvet.com/i/60f/60f485c5606cc5b0118fa64eb2bc5aee.png)
Похожие вопросы
Предмет: Другие предметы,
автор: skynetgrema
Предмет: Биология,
автор: nadixI
Предмет: Физика,
автор: loljan612
Предмет: Алгебра,
автор: alexmail949
Предмет: География,
автор: незнайка1516